PEMEROLEHAN BAHASA KEDUA PADA ANAK: PERAN PAPARAN, LINGKUNGAN SOSIAL DAN STRATEGI PENGASUHAN - Lukman Khoirin; Khoirul Faizin (LPPM IAD Probolinggo, 2025)
This study explores second language (L2) acquisition in children aged 6–12, focusing on the role of language exposure, social environment, and parenting/teaching strategies. Employing a qualitative case study design, three children with different backgrounds were observed: one attending an international school, one enrolled in a regular school with supplementary English lessons, and one studying at a bilingual school. Data were collected through participatory observation at home and school, in-depth interviews with parents and teachers, and document triangulation. The findings indicate that the intensity and consistency of L2 exposure strongly influence fluency, comprehension of instructions, and spontaneous language production. Children with consistent exposure across both home and school demonstrated higher proficiency, including natural code-switching, while those with limited exposure tended to be passive. Supportive social environments and consistent family language policies were also found to enhance L2 development. These results highlight the importance of collaboration between schools and families in providing rich, consistent, and meaningful language input for children. Keywords: second language acquisition; school-age children; language exposure; social environment; parenting strategies